Zonasi Pengelolaan Rumput Laut di Kampung Nelayan Belang-Belang Kecamatan Kalukku, Kabupaten Mamuju, Sulawesi Barat - Intan Yulia Putri T.A.; Mukti Ali; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
Belang-Belang Fishing Village has physical and non-physical characteristics. Physical characteristics analyzed are geographical location and infrastructure including road networks, green open spaces and building functions. Non-physical characteristics include aspects of population and livelihoods. The purpose of this study was to identify the physical and non-physical characteristics of Belang-Belang Fishermen Village, identify seaweed management processes and divide zoning based on physical characteristics and seaweed management processes in the Belng-Belang Fishermen Village Area. The research method is done descriptively with spatial analysis techniques in the form of map overlay techniques. The results of this study indicate that the Belang-Belang Fishermen Village in general has not been well-ordered, so zoning is needed. Zoning is done by identifying the physical characteristics and management processes. The physical characteristics in question are geographical location, infrastructure facilities which include road networks, green open spaces and building functions. Seaweed management is divided into three zones, namely pre-production, production and distribution zones. The pre-production zone is divided into seaweed nursery, seaweed planting and seaweed drying zones. Furthermore, there are no production zones in the research area so seaweed products obtained are directly sold through distribution channels.